CD63 Associates with the αIIbβ3 Integrin-CD9 Complex on the Surface of Activated Platelets - Israels, Sara J.; McMillan-Ward, Eileen M.; Easton, Jeffrey; Robertson, Catherine; McNicol, Archibald (Thrombosis and Haemostasis, 2001)
The tetraspanins are integral membrane proteins expressed on cell surface and granular membranes of hematopoietic cells and have been identified in multi-molecular complexes with specific integrins. In resting platelets, CD63, a member of the tetraspanin superfamily, is present in dense granule and lysosomal membranes and, following platelet activation, translocates to the plasma membrane. In the present study, platelet activation by thrombin leads to incorporation of CD63 into the Triton-insoluble actin cytoskeletal fraction. This incorporation was inhibited by preincubation of platelets with RGDS or EGTA and did not occur in platelets from a patient with Glanzmann’s thrombasthenia, suggesting that it was dependent upon αIIbβ3. In activated platelets, the anti-CD63 MoAb, D545, co-immunoprecipitated CD63 with other surface-labeled proteins, including αIIbβ3 and another tetraspanin, CD9. The association of CD63 with CD9 and αIIbβ3 was not inhibited by preincubation of platelets with RGDS or EGtA. D545 did not inhibit the adhesion of activated platelets to purified extracellular matrix proteins, but significantly decreased adhesion of thrombin-activated platelets to neutrophils in a rosetting assay. D545 also caused disaggregation of platelets stimulated by ADP, but had no effect on aggregation induced by other agonists. These results are consistent with the proposal that CD63 becomes part of an αIIbβ3-CD9-CD63 integrintetraspanin complex in activated platelets – an association that may modulate the function of αIIbβ3-dependent interaction with other cells such as neutrophils.
Keywords: CD antigens; blood platelets; platelet glycoprotein IIb/IIIa complex; platelet activation; cell membrane